Mixed-method evaluation of the Fairer Futures Fund: a £22.2 m public health initiative designed to reduce health inequalities in Birmingham and Solihull (UK) - Litchfield, Ian; Knight, Andy; Howell-Jones, Rebecca; Miller, David; Sweeney, Zoe; Walsh, Mike; Harper, Lorraine (Frontiers in Public Health, 2025)
IntroductionBirmingham and Solihull Integrated Care System created the £22.2 million Fairer Futures Fund to support community-centred collaborative innovation to address long-standing health inequalities in the region. The FFF supports the development of productive and sustainable partnerships between communities, the voluntary sector, and health and social care organisations to deliver three broad categories of projects: multiple small community-located projects; large-scale ‘partnership’ projects led by collaborative partnerships, and a series of system-wide projects intended to support infrastructural interventions across organisations in support of more equitable care.Methods and analysisThe work consists of a mixed-method evaluation conducted over three work packages: One, a qualitative exploration of the factors influencing the design and development of the Fairer Futures Fund programme. Two, a qualitative exploration of the effectiveness of brokered co-design processes and collaborative inter-agency working. Three, a mixed-methods evaluation of all projects, collating and analysing quantitative outputs, contextualised by a qualitative exploration of the experiences of intervention leads and participants. The quantitative data will be summarised using descriptive statistics with the ability of data to be collated and analysed by various shared characteristics across projects using univariable analyses, e.g., paired t-tests (where pre- and post-intervention outcome data are available) and/or multivariable regression analysis to assess the effectiveness of the FFF activities. The qualitative data from across the three work packages will be used in a directed content analysis to populate the Consolidate Framework of Implementation Research.DiscussionThe amount invested, the innovative nature of the funding allocation, and the visibility of the FFF programme warrants this detailed and objective evaluation by experienced researchers and evaluators. To support the success of the FFF, the work will provide both formative and summative findings. Although the precise content and structure of each project is determined by the local communities and collaborating organisations, consistent data collection is supported by the requisite use of a combination of preselected and validated survey tools. This will allow for the collation of larger and comparable data across similar projects. The quantitative data outputs will be contextualised by qualitative data synthesised across work packages using the implementation framework.